Acute kidney injury in HIV‐infected children: comparison of patients according to the use of highly active antiretroviral therapy - Douglas de Sousa Soares; Malena Gadelha Cavalcante; Samille Maria Vasconcelos Ribeiro; Rayana Café Leitão; Ana Patrícia Freitas Vieira; Roberto da Justa Pires Neto; Geraldo Bezerra da Silva Junior; Elizabeth de Francesco Daher (Brazilian Society of Pediatrics, 2016)
Objective: To assess clinical and laboratory data, and acute kidney injury (AKI) in HIV‐infected children using and not using highly active antiretroviral therapy (HAART) prior to admission. Methods: A retrospective study was conducted with HIV‐infected pediatric patients (<16 years). Children who were using and not using HAART prior to admission were compared. Results: Sixty‐three patients were included. Mean age was 5.3 ± 4.27 years; 55.6% were females. AKI was observed in 33 (52.3%) children. Patients on HAART presented lower levels of potassium (3.9 ± 0.8 vs. 4.5 ± 0.7 mEq/L, p = 0.019) and bicarbonate (19.1 ± 4.9 vs. 23.5 ± 2.2 mEq/L, p = 0.013) and had a higher estimated glomerular filtration rate (102.2 ± 36.7 vs. 77.0 ± 32.8 mL/min/1.73 m2, p = 0.011) than those not on HAART. In the multivariate analysis, the use of HAART prior to the admission was a protective factor for AKI (p = 0.036; OR = 0.30; 95% CI = 0.097-0.926). Conclusion: AKI is a common complication of pediatric HIV infection. Use of HAART prior to the admission preserved glomerular filtration and was a protective factor for AKI, but increased medication side effects, such as hypokalemia and renal metabolic acidosis.